Chitin scaffolds derived from the marine demosponge Aplysina fistularis stimulate the differentiation of dental pulp stem cells - Zawadzka-Knefel, Anna; Rusak, Agnieszka; Mrozowska, Monika; Machałowski, Tomasz; Żak, Andrzej; Haczkiewicz-Leśniak, Katarzyna; Kulus, Michał; Kuropka, Piotr; Podhorska-Okołów, Marzenna; Skośkiewicz-Malinowska, Katarzyna (Frontiers in Bioengineering and Biotechnology, 2023)
The use of stem cells for tissue regeneration is a prominent trend in regenerative medicine and tissue engineering. In particular, dental pulp stem cells (DPSCs) have garnered considerable attention. When exposed to specific conditions, DPSCs have the ability to differentiate into osteoblasts and odontoblasts. Scaffolds are critical for cell differentiation because they replicate the 3D microenvironment of the niche and enhance cell adhesion, migration, and differentiation. The purpose of this study is to present the biological responses of human DPSCs to a purified 3D chitin scaffold derived from the marine demosponge Aplysina fistularis and modified with hydroxyapatite (HAp). Responses examined included proliferation, adhesion, and differentiation. The control culture consisted of the human osteoblast cell line, hFOB 1.19. Electron microscopy was used to examine the ultrastructure of the cells (transmission electron microscopy) and the surface of the scaffold (scanning electron microscopy). Cell adhesion to the scaffolds was determined by neutral red and crystal violet staining methods. An alkaline phosphatase (ALP) assay was used for assessing osteoblast/odontoblast differentiation. We evaluated the expression of osteogenic marker genes by performing ddPCR for ALP, RUNX2, and SPP1 mRNA expression levels. The results show that the chitin biomaterial provides a favorable environment for DPSC and hFOB 1.19 cell adhesion and supports both cell proliferation and differentiation. The chitin scaffold, especially with HAp modification, isolated from A. fistularis can make a significant contribution to tissue engineering and regenerative medicine.